Demonstrating impact of allied health professional participation in the NIHR Associate Principal Investigator scheme - Cook, Florence; Gilbody, Nicky; Hunt, Jenny; Knight, Zoe; Sheldrick, Heulwen; Houghton, Lisa; Ewers, Caroline; Caygill, Michael; Speight, Holly; Nazareth, Irwin; Govender, Roganie (BMC health services research, 2025)
Introduction Research impact is defined as an effect, change or benefit to the wider society or services beyond academia. Measuring impact demonstrates benefit and value for money of publicly-funded research. This study evaluates differing levels of impact associated with completion of the National Institute for Health and Care Research Associate Principal Investigator (PI) scheme on SIP SMART2 (Swallowing Intervention Package - Self Monitoring, Assessment & Rehabilitation Training 2); cluster-randomised multi-centre phase II trial with a focus on Prehabilitation of swallowing in head and neck cancer. Methods Data was acquired using two qualitative methods: Reflective virtual discussion group and documentary evidence based on the individual portfolios/checklists of eight accredited Associate PIs. Framework analysis and the evidence of impact model was employed for analysis. Results High level impact was identified on the micro level, with evidence of individual learning and sense of pride in becoming an accredited Associate PI. Medium to high level impact was found at the meso level including taking a leading role in research delivery within own organisations and raising professional profiles amongst the wider team. There were limited examples directly demonstrating macro level impact. Conclusion The Associate PI scheme provides opportunities for professional groups that otherwise might not be involved in clinical trials, promoting equality and inclusiveness with benefits across multiple levels of impact. The current checklist of activities is designed to demonstrate competence in clinical trial delivery and may not currently capture the wider benefits and impact of the scheme. These could be better captured with some additions to the checklist including follow-up on potential impacts accrued beyond the 6-month timefame.